210. Outcomes of Kidney Transplant Recipients with Donor Positive Blood Cultures. (4th December 2021) - Svoronos, Petros; Vijayvargiya, Prakhar; Vaitla, Pradeep; Wynn, James j; Beam, Elena; Parham, Jason; Sohail, Muhammad R; Garrigos, Zerelda Esquer
Abstract: Background: Based on expert opinion, solid organ transplant recipients from donors with bacteremia are treated with 7-14 days of pre-emptive antibiotic therapy (PAT). However, studies addressing necessity, optimal duration of therapy, and outcomes in kidney transplant recipients (KTR) are lacking. Methods: We retrospectively reviewed all kidney transplants performed at our institution from 01/01/2015-01/01/2021 to identify those cases where matched deceased donors had positive blood cultures. Bacteremia was defined per CDC criteria. We analyzed rate of infection in the KTR with the same organism identified in the donor blood culture within 30 days of transplantation. Results: A total of 56 KTRs with donor positive blood cultures were identified. Demographic data are summarized in Table 1. Twenty of 56 cases (35.8%) had bacteremia and 36 (64.2%) had organisms classified as common commensals. The most common organisms in the bacteremia group were Gram-negative bacteria (12/20) and Staphylococcus aureus (6/20). Most common commensals were coagulase-negative staphylococci (26/36) (Table 2). All KTR received preoperative antibiotics at the time of transplantation, primarily cefazolin (15/20), and vast majority received TMP/SMX prophylaxis, for Pneumocystis jirovecii, post-transplant (19/20). PAT was administered in 70% (14/20) cases of bacteremia for a median of 8.5 days (IQR 7-14), while six cases were left untreated (Table 2). In contrast, majority of cases with common commensals were not treated (75%, 27/36). Of the cases treated (9/36), median duration of therapy was 7 days (IQR 5-14). No cases of infection with the same organism identified in the donor blood culture were reported in KTR within 30 days of transplantation. Conclusion: KTR donors with bacteremia who were treated received a median of 8.5 days of PAT with no instances of breakthrough infection. In contrast, majority of donor blood cultures with organisms classified as common commensals were not treated and did well. Future studies are needed to assess whether perioperative antibiotics coupled with TMP/SMX prophylaxis post-transplantation are sufficient in select cases of transplantation from donors with bacteremia. Disclosures: All Authors : No reported disclosures